Isolated surgical left atrial appendage closure: Revisiting utility and indications in a burgeoning era of percutaneous therapy. Issue 6 (25th April 2020) - Hernandez, Paula M.; Divakaran, Sanjay; Adler, Dale S.; Storms, Daniel R.; Kaneko, Tsuyoshi; Mohanty, Bibhu D.
Abstract: Background and Aim: Oral anticoagulation (AC) and percutaneous left atrial appendage (LAA) occlusion are the primary treatment modalities for stroke prevention in atrial fibrillation (AF), but there remains a subset of patients in whom these approaches present excess risk and isolated surgical LAA excision should be considered. We describe a 63‐year‐old female with AF and recurrent thromboembolic events who presented with an acute intraparenchymal hemorrhage and was found to have an intracardiac thrombus. Methods: Given contraindications to AC and LAA occlusion, an isolated LAA surgical excision was pursued. Results: She underwent successful surgical LAA excision and has since remained event‐free. Conclusion: It is important to recall the utility of therapies that have been previously used with success for intracardiac thrombi and still remain as viable options.